Adoption of Breeding and Calf Rearing Practices in Modern Dairy Farms of Gujarat - Gadhavi, DN; Sorathiya, LM; Rathva, AL (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
A study was carried out to compare the breeding and calf rearing practices of modern specialized dairy farms of north and south Gujarat.The data was collected from ten specialized dairy farms, each from the north and south Gujarat. The study revealed that farms of thesouthern region mostly reared buffaloes, which relied on natural service, whereas northern farms mostly reared cows, and AI was morepopular. Around 22.2 and 16.7% of dairy farms preferred pedigreed and sex-sorted semen from the private sector, respectively. Most ofthe dairy farms (60%) purchased frozen semen doses from the co-operative sector. About 20% of dairy farms used sex-sorted semen atthe price of Rs. 2100-3000 per dose. One farm from the north and another one from south were using Delaval® heat detector system.The majority (75%) of the dairy farms adopted the practice of colostrum feeding by allowing for natural suckling. The majority (70%)of the dairy farms provided first colostrum feeding within 2 to 4 hours of calf birth. Some dairy farms (20%) possessed individual calfboxes. From the research finding, it can be concluded that artificial insemination was more famous in north Gujarat. Many specializeddairy farms of north Gujarat were adopting most advanced breeding practices by the use of sex-sorted and pedigreed semen of privatecompanies to produce an offspring of the desired sex, high milk yielding potential and healthy one.
Keywords: Heat detector; Individual calf boxes; Ligation, Pedigreed semen; Sex sorted semen